How does coupling coordination between industrial structure optimization and ecosystem services dynamically affect carbon emissions in the Yellow River Basin? - Xue, Ruixiang; Gu, Runde; Ong, Tzesan (Elsevier, 2025)
In the Yellow River Basin (YRB), the dominance of coal mining and petrochemical industries, coupled with persistent ecosystem degradation, has contributed to increasing carbon emissions (CE). As industrial development has outpaced ecological restoration, aligning industrial structure optimization (ISO) with ecosystem services (ES) has become a strategic priority for emission control. This study examines the dynamic impact of ISO–ES coupling coordination on CE using panel data from 2011 to 2023. The coupling coordination degree model is employed to assess the ISO–ES interaction, while the dynamic spatial Durbin model captures temporal effects, spatial spillovers, and regional heterogeneity of ISO-ES coupling coordination on CE. The findings reveal notable progress in pollution control within the YRB, with steady improvements in ISO-ES coupling coordination; however, carbon emissions continue to grow, albeit slowly. Pronounced spatial spillover effects were also identified, such that ISO-ES coupling coordination impacts not only the YRB's carbon emissions but also those of adjacent regions. Dynamic analysis further found that while ISO-ES coupling coordination significantly reduces carbon emissions, its effect gradually weakens over time. In terms of heterogeneity, the negative impact of ISO-ES coupling coordination on carbon emissions appears to diminish from upstream to downstream regions, exhibiting a converging trend. This study provides empirical evidence to support the implementation of differentiated incentives, dynamic monitoring mechanisms, and the establishment of a regionally coordinated carbon trading system, thereby contributing to the advancement of national clean production transformation.